Bispecific Monoclonal Antibodies Produced by Somatic Cell Fusion Increase the Potency of Tissue Plasminogen Activator - Branscomb, Elizabeth E; Runge, Marschall S; Savard, Christopher E; Adams, Keith M; Matsueda, Gary R; Haber, Edgar (Thrombosis and Haemostasis, 1990)
Bispecific monoclonal antibodies that bind simultaneously to human fibrin and tissue plasminogen activator (tPA) enhance the fibrinolytic potency of tPA. Two bispecific antibodies (F36.23 and F32.1) were generated by somatic cell fusion. Antibody F36.23 derives its tPA binding from monoclonal anti-tPA antibody TCL8 and its fibrin binding from monoclonal antifibrin antibody 59D8. After purification from cell supernatants and ascites by two steps of affinity chromatography, hybrid-hybridoma bispecific antibody F36.23 simultaneously bound tPA and fibrin in solution and in solid-phase assays. In an assay for the lysis of human fibrin monomer, F36.23 increased the fibrinolytic potency of tPA by 5 to 10 fold, regardless of whether the bispecific antibody had been combined with the tPA before or during the assay. Bispecific F36.23 F(ab′)2 also bound tPA and fibrin simultaneously, and the enhancement in fibrinolysis in the presence of F36.23 F(ab′)2 was identical to that in the presence of intact F36.23. The second bispecific antibody, F32.1, was produced by an alternative strategy that has a wider potential for applicaton in other systems. Hybridoma bispecific antibody F32.1 was derived from the fusion of immune splenocytes (in mice immunized with a synthetic oligopeptide representing the amino terminus of the α-chain of human fibrin) with the anti-tPA cell line TCL8. The properties of hybridoma bispecific antibody F32.1 and its F(ab′)2 were indistinguishable from those of hybrid-hybridoma bispecific antibody F36.23 in solid-phase binding assays and in assays of fibrinolysis. Bispecific antibodies produced by somatic cell fusion, particularly in the form of F(ab′)2, may have potential for use in clinical thrombolysis.